Pressure-induced remarkable luminescence-changing behaviours of 9, 10-distyrylanthracene and its derivatives with distinct substituents. (February 2019) - Li, Aisen; Liu, Yingjie; Han, Lu; Xu, Shuping; Song, Chongping; Geng, Yijia; Pan, Lingyun; Xu, Bin; Tian, Wenjing; Zhang, Houyu; Xu, Weiqing; Cui, Haining
Abstract: Piezochromic luminescence behaviours of 9, 10-distyrylanthracene (DSA) derivatives with different substituents based on their single crystal structures were investigated under hydrostatic pressure via a diamond anvil cell (DAC), compared with the anisotropic force produced from grinding. Upon grinding, three single crystals show identifiable blue-shifts in fluorescent spectra because of the disturbance for ordered crystal structure to amorphous state, but nearly sightless color changes. The high-pressure fluorescent experiments applied by DAC reveal three DSA crystals all show large red-shifts. High pressure absorption spectra display that a new charge transfer state appears when -CH3 or -2CN is introduced to DSA and all of them show obvious red-shifts. Once the pressure was relieved gradually to the ambient pressure, the fluorescence and absorption spectra both entirely recovered, indicating this geometric change is reversible in a certain pressure region, which is further confirmed by Raman spectra. The relationships between molecular structures and spectroscopic behaviours were further discussed by their single crystal data. This work provides deep insights into the relationship between molecular structure and photo-physical properties of practical mechanochromic luminescent materials, and is significant in the potential applications of pressure transducers. Graphical abstract: Highlights: Photo-physical behaviors of three DSA crystals with different substituents are disclosed. DSA crystals exhibit different responses to anisotropic/isotropic pressures. Self-recovery of DSA crystals during compression. Remarkably large Red-shift of emission band under pressure is observed. Introduction of -CH3 and –CN to DSA cause a new CT state.